2020
DOI: 10.1097/mao.0000000000002772
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Infections and Outcomes: Experience From a Single Large Center

Abstract: Objective: To review our experience with cochlear implant infections over the past 5 years, the management strategy and to identify predictive factors that led to explantation. Study Design: Retrospective record-base case series of cochlear implant infections. Setting: Tertiary otology and implant center. Patients: All patients who had cochlear implantation over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Earlier explantation in children may be driven by the need to expedite reimplantation, especially among young children where hearing is critical for speech and language development. Our findings are consistent with a prior study of 13 devices showing that the median time to explantation was approximately 7 months, 16 but they contrast with a 35‐year retrospective review of 29 devices that were explanted for CI infection, which demonstrated a median explantation time of 6.6 years. 17 This disparity may partially be explained by our study design focusing on the first 2 years after CI surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier explantation in children may be driven by the need to expedite reimplantation, especially among young children where hearing is critical for speech and language development. Our findings are consistent with a prior study of 13 devices showing that the median time to explantation was approximately 7 months, 16 but they contrast with a 35‐year retrospective review of 29 devices that were explanted for CI infection, which demonstrated a median explantation time of 6.6 years. 17 This disparity may partially be explained by our study design focusing on the first 2 years after CI surgery.…”
Section: Discussionsupporting
confidence: 87%
“…The need for explantation in the management of CI infections is uncommon with rates between 0.65% and 1.8% of CI recipients [37,[41][42][43]. Attempts initially at device salvage should be considered given favourable outcomes with this approach [14,24].…”
Section: Investigation and Management Of Cochlear Implant Associated ...mentioning
confidence: 99%
“…This pain often presents in a delayed timeframe postoperatively, with a mean of 5.8 years in one study 4 . Vijendren et al recently proposed three possible causes for pain at the CI site: 1) biofilm of the device causing localized inflammation, 2) neurogenic pain, and 3) psychogenic pain 7 . To date, no study has systematically evaluated a cohort of pediatric patients that have undergone device removal in an attempt to uncover the etiology of persistent idiopathic CI pain.…”
Section: Introductionmentioning
confidence: 99%